Air pollution from forest burning as environmental risk for millions of inhabitants of the Brazilian Amazon: an exposure indicator for human health - Igor Neves de Oliveira; Beatriz Fátima Alves de Oliveira; Ismael Henrique da Silveira; Lúbia Maieles Gomes Machado; Juliana Wotzasek Rulli Villardi; Eliane Ignotti (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2023)
Abstract: In this study, we propose an indicator of air pollution exposure to identify potential hazardous areas for human health in the Amazon and Central-West Regions of Brazil from 2010 to 2019. This indicator aggregates both concentrations and time of exposure to fine particulate matter (PM2.5), according to the current limit recommended by the World Health Organization (WHO). We used daily PM2.5 averages obtained from the Brazilian Health Integrated Environmental Information System (SISAM) to calculate the percentages of days with PM2.5 concentrations exceeding the limit of 15µg/m³ per year and per month. From 2010 to 2019, the months from August to October presented the largest areas and the highest percentages of days with unacceptable pollution concentration values, harmful to human health. These areas were concentrated in the Arc of Deforestation. Therefore, 60% of the residents of the Amazon and Central-West regions were subjected to inadequate air quality for approximately six months per year. The proposed indicator is reproducible and appropriate to monitor areas of exposure and risk for human health.